Strategi Memperkuat Persekutuan Dalam Pembinaan Iman Lansia - Benget Parningotan (Institut Agama Kristen Negeri (IAKN) Ambon, 2024)
In Indonesia, the number of elderly people continues to increase. In facing old age, many elderly people face physical, psychological and spiritual challenges. The church has an important role in fostering faith and providing spiritual support for the elderly. There are special needs of the elderly both physically, psychologically, socially and especially spiritually that need attention. Often these needs have not been met optimally in many places. The existing fellowship for the elderly is still not strong enough and effective in accompanying the elderly and fostering their faith at the end of life. Many elderly whose faith falters, despair or tend to withdraw from church life when facing physical and mental problems in old age. Strategic efforts from the church are needed to strengthen the existing fellowship for the realization of effective faith formation of the elderly. Therefore, the purpose of this study is to provide input and contributions for churches and elderly fellowship leaders on how to design and implement appropriate strategies in strengthening fellowship for the formation of Christian elderly who remain firm in faith. This research uses qualitative methods with in-depth interview techniques to the elderly of GPIN Bukit Asam Tanjung Enim. The results showed that effective strategies include: Training elderly fellowship leaders, Conducting Bible studies, Conducting home visits to the elderly, Organizing field worship, and Using digital media to share God's word. By implementing the right strategies, the church can strengthen the elderly fellowship to foster the faith of the elderly.